Efektivitas Thin Cookies Daun Kelor untuk Meningkatkan Status Gizi pada KEK Remaja - Wanggy, Desta Marsahusna; Marsum, Marsum; Rahayu, Sri (Universitas Malahayati, 2026)
ABSTRACT CED in adolescent girls is caused by an imbalance in energy and protein intake. Moringa leaves (Moringa oleifera), which is rich in nutrients, can be processed into thin cookies as Supplementary Feeding (PMT) to improve BMI. Analyzing the effectiveness of giving thin cookies Moringa leaves towards improving BMI with chronic energy deficiency (CED) in adolescent girls in the Parakan Community Health Center working area. Quasy experiment by using pretest-posttest control group design using purposive sampling technique. The total sample was 52 young women with inclusion criteria. Then, divided into 2 groups with 26 respondents each, namely the intervention group given thin cookies Moringa leaves 25 gr and control group cookies Regal 25 grams consumed 3 pieces/day for 4 weeks. Data analysis using Paired Test, Independent Test and Mann Whitney. Giving thin cookies Moringa leaves were proven to be effective in improving BMI in CED adolescent girls with a p value 0.001. With an average difference in the increase in nutritional status in the treatment group (0.9958 kg/m2) greater than the control group (0.4273 kg/m2). The provision of thin moringa leaf cookies has been proven effective in improving BMI in adolescent girls with CED. Keywords: Moringa Leaves, Thin Cookies, CED Adolescent Girls, BMI ABSTRAK KEK pada remaja putri disebabkan oleh ketidakseimbangan asupan energi dan protein. Daun kelor (Moringa oleifera), yang kaya nutrisi, dapat diolah menjadi thin cookies sebagai Pemberian Makanan Tambahan (PMT) untuk meningkatkan IMT. Menganalisis efektifitas pemberian thin cookies daun kelor (moringa Leaves) terhadap peningkatan IMT dengan kekurangan energi kronik (KEK) pada remaja putri di wilayah kerja Puskesmas Parakan. Quasy experimentdengan menggunakan pretest-posttest control group design menggunakan teknik purposive sampling. Jumlah sampel 52 remaja putri dengan kriteria inklusi. Kemudian, dibagi menjadi 2 kelompok dengan masing-masing 26 responden yaitu kelompok intervensi yang diberikan thin cookies daun kelor 25 gr dan kelompok kontrol cookies regal 25 gr yang dikonsumsi 3 keping/hari selama 4 minggu. Analisis data menggunakan Paired Test, Independent Test dan Mann Whitney. Pemberian thin cookies daun kelor terbukti efektif dalam meningkatkan IMT pada remaja putri KEK dengan nilai p0,001. Dengan rata-rata selisih peningkatan IMT pada kelompok perlakuan (0,9958 kg/m2) lebih besar dari kelompok kontrol (0,4273 kg/m2). Pemberian thin cookies daun kelor terbukti efektif dalam meningkatkan IMT pada remaja putri dengan KEK. Kata Kunci: Daun Kelor, Thin Cookies, Remaja Putri KEK, IMT.